Novel POLE pathogenic germline variant in a family with multiple primary tumors results in distinct mutational signatures. Issue 1 (20th November 2018) - Castellsagué, Ester; Li, Rui; Aligue, Rosa; González, Sara; Sanz, Judit; Martin, Edgar; Velasco, Àngela; Capellá, Gabriel; Stewart, Colin J. R.; Vidal, August; Majewski, Jacek; Rivera, Barbara; et al.
Abstract: We describe a family in which four siblings exhibited multiple or classic colonic polyposis with or without colorectal carcinoma (CRC). One female developed three primary tumors, including CRC and carcinomas of the ovary and breast. Whole‐exome sequencing of germline DNA from affected and unaffected individuals revealed a novel missense mutation in the exonuclease domain of POLE (c.833C>A; p.Thr278Lys) associated with a highly penetrant, autosomal‐dominant inheritance pattern. Functional studies in yeast and demonstration of a high mutational burden in the available tumors confirmed the pathogenicity of the novel variant. Prominent POLE‐deficient somatic mutational signatures were seen in the CRCs, but in contrast, a mutational signature typical of concomitant tumoral loss of POLE and mismatch‐repair function (POLE‐exo * /MSI) was noted in the breast cancer. The breast cancer also showed distinctive pathological characteristics that reflect the presence of both the germline POLE variant and the secondary somatic MMR alterations. Abstract : In a family of four siblings with colonic polyposis and colonic and extracolonic tumors, we found a novel variant in POLE gene (c.833C>A; p.Thr278Lys) that we proved to be pathogenic by functional assays in yeast and high mutational burden in tumors. Prominent POLE‐deficient somatic mutational signatures were seen in the CRCs, but a mutational signature typical of concomitant tumoral loss of POLE and mismatch repair function (POLE‐exo * /MSI) was noted in the breast cancer.